A Theoretical Review on the Role of English as a Foreign Language Teachers’ Self-Disclosure in Shaping Classroom Climate and Immediacy - Qin, Jing (Frontiers in Psychology, 2022)
Teachers’ interpersonal communication skills and strategies have been widely considered effective pedagogical tools in academia. Despite the growing research in this area, unraveling the power of EFL teachers’ self-disclosure in shaping classroom climate and immediacy has been relatively left intact. To fill the gap and provide new insights into this strand of research, the present article was an effort to present a theoretical analysis of the interplay of self-disclosure, classroom climate, and immediacy. In so doing, the definitions, conceptualizations, dimensions, underlying theories, and empirical evidence in support of the interaction among these three constructs were presented. Moreover, practical implications for EFL teachers, teacher trainers, and L2 scholars were provided to raise their awareness of interpersonal communication skills and their outcomes in academia. Finally, the study provided some suggestions for further research in this line of inquiry.